PENGARUH PENERAPAN MODEI PEMBEIAJARAN KOOPERATIF TIPE THINK TAIK WRITE TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KEIAS XL LPA SMA PGRL 1 PADANG - Tria Mayasari (Jurnal Edukasi dan Penelitian Matematika, 2021)
The purpose of this research was to describe the development of students’ mathematical communication abilities and investige whether mathematical communication abilities of students whose using cooperative learning model think talk write type (TTW) be tter than students’ mathematical communication abilities whose using conventional learning. This research was combination of descriptive and quasi- experimental research which used Static Group Design. The conclusion of this research are 1) Mathematical communication abilities of students has increased at present indicators of mathematical statements, either orally, in writing, drawings, and diagrams and draw conclusions indicators, compiling evidence, reasoning, or proof against option solutions. For mathematical manipulations indicator of students' abilities fluctuate. 2) Students’ mathematical communication abilities whose using cooperative learning think talk write type (TTW) better than students’ mathematical communication abilities whose using conventional learning. It can be concluded that cooperative learning model TTW affect of students' mathematical communication abilities.Keywords – cooperative Iearning modeI, Think TaIk Write, MathematicaI communication abiIities